Lipid Peroxidation and Antioxidant Status in Nonobese Type 2 Diabetes Mellitus. (22nd October 2014) - Khemka, Vineet Kumar; Choudhuri, Subhadip; Ganguly, Anirban; Ghosh, Arindam; Bir, Aritri; Banerjee, Anindita
Abstract : The aim of the study was to investigate the association between lipid peroxidation and antioxidant status in nonobese type 2 diabetes mellitus (T2DM) and further to correlate whether their significant association is putatively associated with the pathogenesis of T2DM. A number of 102 nonobese T2DM subjects and 95 nondiabetic subjects as healthy controls were enrolled in this cross-sectional study. Serum samples were collected in cryovials for malondialdehyde (MDA) and thiol assays. Total thiol or sulfhydryl (–SH) groups in peripheral blood mononuclear cells (PBMCs) and sera, as well as level of MDA, a marker for lipid peroxidation in serum, were measured spectrophotometrically. Serum MDA level was found significantly higher whereas serum and PBMC total thiol levels were diminished significantly among nonobese T2DM subjects compared to HC subjects. Moreover, serum MDA level is found to have a significant inverse correlation with serum total thiol and PBMC thiol levels among DM subjects, but no significant correlation was observed in HC individuals. A significant inverse correlation between serum MDA and serum total thiol levels among nonobese T2DM subjects suggests a close association of increased oxidative stress with decreased antioxidant status in nonobese T2DM.